2017
DOI: 10.1002/jctb.5221
|View full text |Cite
|
Sign up to set email alerts
|

The ability of Achromobacter sp. KW1 strain to biodegrade isomers of chlorotoluene

Abstract: Background The isomers of chlorotoluene (2‐chlorotoluene, 3‐chlorotoluene and 4‐chlorotoluene) are considered to be toxic and to have a negative impact on humans and the environment. Therefore, issues related to their removal from the natural environment have become of increasing interest. Results The morphology of cells and colonies after long‐term metabolic stress was significantly modified. Metabolic stress is suggested to be a determinant of bacteria cell surface properties. The chlorine atom position in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Woertz et al [40] also found that sodium dodecyl sulfate (SDS) lowered toluene biodegradation rates by Exophialalecanii-corni , while Tween 20 increased its elimination. In accordance with the present results, previous studies of Pacholak et al [41] have demonstrated that saponins extracted from Sapindus mukorossi fruits elevated the level of 4-chlorotoluene biodegradation and simultaneously negatively affected the degradation of toluene.…”
Section: Resultssupporting
confidence: 94%
“…Woertz et al [40] also found that sodium dodecyl sulfate (SDS) lowered toluene biodegradation rates by Exophialalecanii-corni , while Tween 20 increased its elimination. In accordance with the present results, previous studies of Pacholak et al [41] have demonstrated that saponins extracted from Sapindus mukorossi fruits elevated the level of 4-chlorotoluene biodegradation and simultaneously negatively affected the degradation of toluene.…”
Section: Resultssupporting
confidence: 94%
“…Waste motor oil and diesel were used for biosurfactants production. They are stable after incubations up to 100 ∘ C, in the presence of various NaCl concentrations (20-150 g L -1 ) and over a wide pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The CMC were identical for the two biosurfactants at about 800 mg L -1 .…”
Section: Resultsmentioning
confidence: 93%
“…Bioremediation is widely known to be economical, versatile and ecologically accepted as cleaning technology. In recent years, an increased interest in microbiological investigations has been devoted to bioremediation of oil contaminated sites using various microorganisms such as bacteria and fungi . The conversion of complex structures into simpler forms, using microorganisms, is known as microbial degradation and it is generally an eco‐friendly process, which can provide a safe solution for oil pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptation can lead to a genetic mutation or induction or depression of a specific enzyme [45]. Various studies showed a positive role of the acclimation of Pseudomonas sp and Achromobacter sp on the degradation of refractory pollutants [46,47].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%